Pengembangan Bahan Ajar Berbasis Pembelajaran Berdiferensiasi Materi Operasi Perkalian dan Pembagian Bilangan Cacah Kelas III A MI Terpadu Berkah - Muhammad Syabrina; Nur Husna Aulia; Nurlaili Jannah Ciptaningtyas; Milia Milia (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to develop teaching materials based on differentiated learning for third-grade students of MI Terpadu Berkah Palangka Raya City and determine its effectiveness through direct trials in the classroom. The research method used is research and development (R&D) with a field trial stage. The research subjects were fourth-grade students. Data collection techniques were carried out through observation, questionnaires, and documentation. The results of the questionnaire from material experts, design and field trials showed that this interactive learning media was very appropriate, with a percentage score of 100% including the qualification of